Building between the two rivers : an introduction to the building archaeology of ancient Mesopotamia - Anastasio, Stefano (Archaeopress Archaeology, 2020)
This volume introduces university students and scholars of Near Eastern archaeology to 'Building archaeology' methods as applied to the context of Ancient Mesopotamia. It helps the reader understand the principles underlying this discipline and to realise what knowledge and skills are needed, beyond those that are specific to archaeologists.